Inspired by the Nature: A Post-printed Strategy to Efficiently Elaborate Parahydrophobic Surfaces - Jordy Queiros Campos; Caroline R. Szczepanski; Marie Gabrielle Medici; Guilhem Godeau (Biomimetics, 2022)
The lack of drinkable water is one of the most significant risks for the future of the humanity. Estimates show that in the near future, this risk will become the origin of massive migrations leading to humanitarian disaster. As consequence, the development of solutions to provide water is becoming ever more critical, and a significant effort is devoted to identifying new sources of water. Among the developed strategies, fog harvesting, which takes advantage of atmospheric water to provide potable water, is a solution of interest due to its potential in sustainable development. Unfortunately, this approach suffers from low yield. In the present work, we take inspiration from living species to design and elaborate surfaces with high potential for water harvesting applications. This work takes advantage of 3D-printing and post-printing functionalization to elaborate a strategy that allows modelling, printing, and functionalization of surfaces to yield parahydrophobic behavior. The roughness and surface morphology of the prepared surfaces were investigated. These characteristics were then related to the observed wettability and potential of the functionalized interfaces for water harvesting applications. This work highlights significant variations in surface wettability via surface modification; strong hydrophobic behavior was observed via modification with linear carboxylic acids particularly for surfaces bearing vertical blades (plate with vertical blades and grid with vertical blades).